علاقة وزن الحامل بالولادة الباكرة - الأيوب جهاد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة على 1485 حامل في قسم التوليد بمشفى الأسد الجامعي باللاذقية في الفترة ما بين 1/7/2006 و 1/5/2008 وقسمت الحوامل إلى ست مجموعات: المجموعة الأولى وعددها 109 أوزان الحوامل فيها أقل من 55 كغ والمجموعة الثانية وعددها 175 أوزان الحوامل فيها بين 56-60 كغ والمجموعة الثالثة وعددها 483 أوزان الحوامل فيها بين 61-70 كغ والمجموعة الرابعة وعددها 459 أوزان الحوامل فيها بين 71-80 كغ والمجموعة الخامسة وعددها 172 أوزان الحوامل فيها بين 81-90 كغ والمجموعة السادسة وعددها 87 أوزان الحوامل فيها أكبر من 90 كغ وكان هدف هذه الدراسة تحديد نسبة حدوث الولادة الباكرة في كل مجموعة. إن الولادة الباكرة كانت بنسبة 20.93% عند الخروسات و 21.21% عند ولودات المجموعة الأولى مقابل20.48%, 19.56% في المجموعة الثانية و6.63%, 6.98% في المجموعة الثالثة و7.03%, 8.46% في المجموعة الرابعة و11.53%, 11.70% في المجموعة الخامسة و20.51%, 18.75% في المجموعة السادسة. This study has been carried out on 1485 pregnant women in the Obstetrics and Gynecology Department at AL-Assad University Hospital in Lattakia between 1/7/2006 and 1/5/2008. These were divided into 6 groups: The first group included 109 whose weights were <55 Kg, the second group included 175 whose weights were 56-60 Kg, the third group included 483 whose weights were 61-70 Kg, the fourth group included 459 whose weights were 71-80 Kg, the fifth group included 172 whose weights were 81-90 Kg, and the sixth group included 87 whose weights were > 90 Kg. The purpose of this study was to determine the preterm labor ratios of each group. The ratios of the preterm labor for primi were 20.93 and 21.21% for multi in the first group vis-à-vis 20.48, 19.56% in the second group, 6.63, 6.98% in the third group, 7.03, 8.46% in the fourth group, 11.53, 11.70% in the fifth group, and 20.51, 18.75% in the sixth group.